Germination response of MR 219 rice variety to different exposure times and periods of 2450 MHz microwave frequency - Talei, Daryush; Valdiani, Alireza; Mahmood, Maziah; Mohsenkhah, Mohammad (Hindawi Publishing Corporation, 2013)
Germination is a key process in plants' phenological cycles. Accelerating this process could lead to improvment of the seedling growth as well as the cultivation efficiency. To achieve this, the effect of microwave frequency on the germination of rice seeds was examined. The physiological feedbacks of the MR 219 rice variety in terms of seed germination rate (GR), germination percentage (GP), and mean germination time (MGT) were analyzed by exposing its seeds to 2450 MHz of microwave frequency for one, four, seven, and ten hours. It was revealed that exposing the seeds to the microwave frequency for 10 hours resulted in the highest GP. This treatment led to 100% of germination after three days with a mean germination time of 2.1 days. Although the other exposure times of microwave frequency caused the moderate effects on germination with a GPa3 ranged from 93% to 98%, they failed to reduce the MGTa3. The results showed that ten-hour exposure times of microwave frequency for six days significantly facilitated and improved the germination indices (primary shoot and root length). Therefore, the technique is expected to benefit the improvement of rice seed germination considering its simplicity and efficacy in increasing the germination percentage and rate as well as the primary shoot and root length without causing any environmental toxicity.